USWATUN HASANAH LEARNING MODELS THROUGH CURRENT TECHNOLOGY - Junaidi; Kustati , Martin; Sepriyanti, Nana (As-Sulthan Journal of Education, 2026)
Learning is a crucial process undertaken by educators and students. This process requires the use of a variety of models and methods to create a more engaging and effective learning environment. The importance of innovation in learning methods is inseparable from the rapid development of technology. Technology can be utilized to support classroom learning activities, provide broader resources, and facilitate interaction between educators and students. This study adopted a qualitative approach with a document content analysis research design, focusing on the learning methods and models used. Several important findings in this study include the implementation of the synectic learning model, the application of the uswah hasanah method, and the collaboration between the two in Islamic Religious Education (PAI) learning. These findings contribute to the development of a more effective learning process, in which modern technology, including social media, plays an increasingly important role. Thus, the resulting learning becomes more collaborative, innovative, and relevant to the needs of the times, thereby increasing student motivation and learning outcomes. The implementation of these models and methods is expected to provide a memorable and meaningful learning experience..